The Analysis of Physical Acitivity and Physical Fitness Level of Lecturers and Employees of ITB in 2018 - Ramania, Nia Sri; Apriantono, Tommy; Syafriani, Rini; Kusnaedi, K (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
The level of fitness is a vital aspect that plays an important role in measuring the risk of disease or a person's productivity level. Therefore, this study was aimed at determining and analysing the profile of physical activity and the level of fitness of lecturers and employees in ITB environment. The samples were 219 lecturers and staffs of ITB (110 males and 109 females) who were in 45 - 60 years age range (height 159.7 ± 8.1 cm, body weight 65.0 ± 12.5 kg, BMI 25.5 ± 4.3).  All participants completed series of tests such as the VO2max test with the Rockport test method, anthropometric testing, and filling out a physical activity questionnaire using the International Physical Activity Questionnaire (IPAQ) method. The results of this study explained that, of the 219 subjects in this study, most of the subjects had the endomorph type. The VO2max test showed that 49% of the subjects were in the good VO2max category, which was in the range of 31 ml / kg / min to 40 ml / kg / min. Meanwhile, the IPAQ measurement showed that 41% of the total subjects had a low habit of physical activity. This study revealed quantitatively that low physical activity had a high risk of causing obesity and overweight on a person. On the other hand, this study showed that 24% of the total subjects who did a high intensity activity (exercise, etc.) were in the above average VO2max level compared to other subjects. In the end, this research wants to encourage every academic community or other employees to balance the work time with resting patterns, nutrition, and doing regular exercise.